The Effect of Fiscal Decentralization on Economic Convergence amongst Regions in Java Island (Spatial Econometric Approach) - Anggraeni, Rima Melati; Khusaini, Mohamad; Prasetyia, Ferry (Sanskara Akuntansi dan Keuangan, 2024)
Convergence mechanism is needed in order to reduce regional inequality. This study aimed to examine the existence of economic convergence and analyze the effect of fiscal decentralization on economic convergence with spatial econometric approach. Local own-source revenue, balance funds, personnel expenditure and capital expenditure as proxies for fiscal decentralization indicator. Using dynamic convergence analysis, the existence of beta absolute and conditional convergence are confirmed in this study. From the estimation result, local own-source revenue, balance funds, personnel expenditure have significant role on per capita income growth, while capital expenditure has not been effective in supporting growth. If fiscal decentralization indicators are added and spatial aspects are considered in the model, it will cause an increase in the convergence rate. Improving the quality of spending is the main key to accelerating convergence.